Production of Carbonaceous Material from Avocado Peel for Its Application as Alternative Adsorbent for Dyes Removal - Contreras-Villacura, E (Chemical Industry Press, 2016)
Adsorption processes have received special attention for contaminants removal thanks to their capability to generate effluents with high quality as well as their simple design. In the current work, the agro-waste residue avocado peel is proposed to be used as alternative to conventional activated carbons whose use is sometimes restricted to high costs, upgraded by their exhausting after long term operations. The carbonization procedure was optimized and analyzed through factorial design and response surface methodology by evaluating temperature (400-900 °C) and time (30-90 min) effects: optimal conditions were found at 900 °C and 65 min, generating an adsorbent with 87.52 m2·g- 1 of BET surface area, a mesopore volume of 74% and a zero point charge at 8.6. The feasibility of the carbonaceous material was proved for the removal of a variety of dyes by investigating substrate (10-50 mg·L- 1) and solid (0.5-20 g·L- 1) concentration effects and statistical significance: complete removal of Naphthol Blue Black and Reactive Black 5 was reached under optimal conditions (10 mg·L- 1 and 20 g·L- 1 of dye and solid, respectively), while Basic Blue 41 was eliminated by using 13.4 g·L- 1 of the adsorbent. Overall, dyes removal by adsorption on carbonized avocado peel is presented as a promising technology due to the low cost and easy availability of the precursor, as well as the straightforward generation, the satisfactory characteristics and the proved adsorption capacity of the adsorbent. © 2015 The Chemical Industry and Engineering Society of China, and Chemical Industry Press. All rights reserved.